Proceeding of Mulawarman Pharmaceuticals Conferences 2015
DOI: 10.25026/mpc.v2i1.40
|View full text |Cite
|
Sign up to set email alerts
|

Analisa Tingkat Kepatuhan Penggunaan Terapi Obat Oral Antidiabetik (Oad) Pada Pasien Diabetes Mellitus Di Instalasi Rsud. A.W Sjahranie

Abstract: Patient compliance in taking medication drug an important role in the success of long-term treatment of chronic and degenerative disease, for example Diabetes Mellitus (DM). ABSTRAKKepatuhan pasien dalam mengkonsumsi obat berperan penting dalam keberhasilan pengobatan jangka panjang prnyakit kronis dan degeneratif, salah satunya Diabetes Mellitus (DM). Terapi farmakologi Diabetes Mellitus terdiri dari 2 yaitu injeksi insulin dan obat oral. Obat Oral Antidiabetik (AOD) yang harus minum setiap hari akan berdampa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…Diabetes mellitus patients require pharmacological therapy in the form of oral antidiabetic drugs which must be consumed for a long period of time even for life. Compliance of DM patients when taking oral antidiabetic drugs is needed to achieve long-term treatment success [13] . Based on table 1, it was found that the level of compliance of respondents in using type 2 diabetes mellitus drugs at Soppeng Hospital was low compliance 43.3%.…”
Section: Patient Compliance Patterns On Therapeutic Success Of Type 2...mentioning
confidence: 99%
See 2 more Smart Citations
“…Diabetes mellitus patients require pharmacological therapy in the form of oral antidiabetic drugs which must be consumed for a long period of time even for life. Compliance of DM patients when taking oral antidiabetic drugs is needed to achieve long-term treatment success [13] . Based on table 1, it was found that the level of compliance of respondents in using type 2 diabetes mellitus drugs at Soppeng Hospital was low compliance 43.3%.…”
Section: Patient Compliance Patterns On Therapeutic Success Of Type 2...mentioning
confidence: 99%
“…A person who has a job with quite dense activities tends to forget or be irregular in using drugs and does not have time for routine control to the hospital which results in patients being late in redeeming drugs. on the other hand, lack of physical activity can also be a risk factor for insulin resistance, a trigger for type 2 diabetes mellitus [13] . Based on the data shown in table 3, a significance value of 0.527 was obtained, which means statistically there is no relationship between work and compliance (p>0.05).…”
Section: Patient Compliance Patterns On Therapeutic Success Of Type 2...mentioning
confidence: 99%
See 1 more Smart Citation
“…Pasien DM membutuhkan terapi farmakologis berupa obat antidiabetes oral yang harus dikonsumsi dalam jangka waktu yang lama. Kepatuhan pasien DM dalam mengkonsumsi obat antidiabetes oral sangat diperlukan untuk mencapai keberhasilan pengobatan jangka panjang (Fitriani et al, 2015). Ketidakpatuhan dalam minum obat secara rutin dapat mengakibatkan terjadinya komplikasi, risiko rawat inap, dan biaya yang lebih tinggi (Srikartika et al, 2015).…”
Section: Pendahuluanunclassified
“…Compliance is assessed as a positive and good personal activity. The desired choice aims for a person to act in accordance with the law, community norms, regulations, and a person's own will which has a strong influence while choosing to consider it (Fitriani et al, 2015). There are four signs of compliance, namely the right instructions for use, the right amount of medication taken, the right interval of use, and the right duration of use (Fauziah, 2016).…”
Section: Introductionmentioning
confidence: 99%